About Two Manners of Use Weighted Least Squares Approach in Fuzzy Statistics - Ciprian Costin Popescu; Supian Sudradjat (Universitas Islam Bandung, 2008)
Two fuzzy statistical models are generalized and extended to the weighted models. The new regression problems are solved and compared with the originals.